Translating taboo words in health care texts from English into Swahili in Kenya. Issue 2 (3rd April 2022) - Orang'i, Douglas Ondara
Abstract: This article explores the translation of taboo words in health care texts from English source texts into Swahili. The article seeks to describe the translation of taboo words and identify the translation strategies used to overcome the constraints. It is expected that translators act as cultural mediators who ensure that translations correspond to the target culture's expectations without traumatising them. The study is theoretically anchored in Descriptive Translation Studies. The taboo words that emerged in the texts broadly fall under body parts, sex, bodily functions and defaecation. The findings indicate that Swahili translators resort to the strategies of translation with a more general word, use of a neutral or less expressive word, cultural substitution, translation by paraphrase, substitution and a blend of translation with a more general word and substitution to overcome taboo-imposed constraints. Equally, it was established that the strategies used lean towards euphemism and that leads to the conclusion that euphemism norms are very important in the translation of Swahili health care texts.